Cosmological constraints on induced gravity dark energy models. Issue 5 (31st May 2016) - Ballardini, M.; Finelli, F.; Umiltà, C.; Paoletti, D.
Abstract: We study induced gravity dark energy models coupled with a simple monomial potential ∝ σ n and a positive exponent n . These simple potentials lead to viable dark energy models with a weak dependence on the exponent, which characterizes the accelerated expansion in the asymptotic attractor, when ordinary matter becomes negligible. We use recent cosmological data to constrain the coupling γ to the Ricci curvature, under the assumptions that the scalar field starts at rest deep in the radiation era and that the gravitational constant in the Einstein equations is compatible with the one measured in a Cavendish-like experiment. By using Planck 2015 data only, we obtain the 95 % CL bound γ < 0.0017 for n =4, which is further tightened to γ < 0.00075 by adding Baryonic Acoustic Oscillations (BAO) data. This latter bound improves by ∼ 30 % the limit obtained with the Planck 2013 data and the same compilation of BAO data. We discuss the dependence of the γ and ̇ G N / G N ( z =0) on n .